Comparison of photosynthetic performances of marine picocyanobacteria with different configurations of the oxygen-evolving complex - Partensky, Frédéric; Mella-Flores, Daniella; Six, Christophe; Garczarek, Laurence; Czjzek, Mirjam; Marie, Dominique; Kotabová, Eva; Felcmanová, Kristina; Prášil, Ondřej (Photosynthesis research, 2018)
The extrinsic PsbU and PsbV proteins are known to play a critical role in stabilizing the Mn4CaO5 cluster of the PSII oxygen-evolving complex (OEC). However, most isolates of the marine cyanobacterium Prochlorococcus naturally miss these proteins, even though they have kept the main OEC protein, PsbO. A structural homology model of the PSII of such a natural deletion mutant strain (P. marinus MED4) did not reveal any obvious compensation mechanism for this lack. To assess the physiological consequences of this unusual OEC, we compared oxygen evolution between Prochlorococcus strains missing psbU and psbV (PCC 9511 and SS120) and two marine strains possessing these genes (Prochlorococcus sp. MIT9313 and Synechococcus sp. WH7803). While the low light-adapted strain SS120 exhibited the lowest maximal O2 evolution rates (Pmax per divinyl-chlorophyll a, per cell or per photosystem II) of all four strains, the high light-adapted strain PCC 9511 displayed even higher PChlmax and PPSIImax at high irradiance than Synechococcus sp. WH7803. Furthermore, thermoluminescence glow curves did not show any alteration in the B-band shape or peak position that could be related to the lack of these extrinsic proteins. This suggests an efficient functional adaptation of the OEC in these natural deletion mutants, in which PsbO alone is seemingly sufficient to ensure proper oxygen evolution. Our study also showed that Prochlorococcus strains exhibit negative net O2 evolution rates at the low irradiances encountered in minimum oxygen zones, possibly explaining the very low O2 concentrations measured in these environments, where Prochlorococcus is the dominant oxyphototroph.
Keywords: Photosynthesis; genom bakteriální; Chlorophyll; Models, Molecular; Photosystem II Protein Complex; Photoacclimation; Oxygen minimum zones; Synechococcus; světlo; Marine cyanobacteria; chlorofyl; molekulární modely; bakteriální proteiny; Light; sinice; Oxygen-evolving complex; fotosystém II (proteinový komplex); Oxygen; kyslík; Flow Cytometry; Prochlorococcus; Photosystem II; Bacterial Proteins; průtoková cytometrie; Genome, Bacterial; Cyanobacteria; fotosyntéza